Sarcoidosis Epidemiology: Race Matters - Hena, Kerry Maryse (Frontiers in Immunology, 2020)
Rather than a single disease entity, sarcoidosis may be a constellation of “sarcoidoses” with a characteristic pattern of organ involvement and clinic course, depending upon the triggering exposure and underlying epidemiologic factors such as race. This review examines the racial disparities inherent to sarcoidosis disease course and mortality and discusses factors that may be responsible for these findings. In the United States, black patients with sarcoidosis experience more severe pulmonary disease, more multiorgan involvement, and an overall worse prognosis with higher rates of hospitalization and mortality. Beyond inherent genotype, ascertainment and access to medical care, physician implicit bias, and patient perceived discrimination likely play a role. Moving forward, epidemiologic concepts can be used to formulate strategies for control, treatment, and even prevention of disease in black Americans at risk for developing life-altering or life-threatening sarcoidosis phenotypes. Identification and rectification of modifiable risk factors such as socioeconomic status, lack of insurance, and financial barriers to care as well as the incorporation of implicit bias training for physician will likely lead to improvement in discordant outcomes.